INDEKS KUALITAS AIR RAWA LEBAK DELING UNTUK BUDIDAYA PERIKANAN ALAMI - Irkhamiawan Ma’ruf; Rahmad Kurniawan; Khusnul Khotimah (Universitas Sriwijaya, 2018)
ABSTRACTAs a common properti, fisheries management in swamps need to be made to provides economic benefits for the parties on the one side (especially the community), and the sustainability of the ecosystem itself on the other side. Current conditions need to be obtained to formulate swamp resource management in a sustainable manner by reducing fishing activities with aquaculture activities. Aquaculture, besides providing greater income, can also control fishing activities and reduce pressure on the swamp ecosystem. The study was conducted in Rawa Deling, Deling Village, Pangkalan Lampam Sub-District, OKI District. Water quality measurements are carried out for 5 months, from March 2018 to July 2018 in 4 stations with differences depth and vegetation. Water quality analysis is carried out to get an overview of the swamp condition. Water quality data will determine the feasibility and treatment needed for aquaculture. The results of water quality measurements showed that temperature parameter values ranging from 28.1 - 32.2 oC, depths of 0.7 - 5 m, brightness of 20 - 50 cm, TDS 17 - 35 mgL-1, pH 4.1 - 5, DO 1 , 7 - 4.1 mgL-1, phosphate <0.060 - <0.090 mgL-1, total nitrogen 12.50 - 38.90 mgL-1, ammonia 0.68 - 0.93 mgL-1. Measuring water quality shows the potential for deling swamps to be developed in an effort to increase fish stocks and aquaculture activities.Keywords : lebak lebung swamps, sustainable fisheries management, swamp water quality